2015
DOI: 10.1080/10408398.2015.1060940
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A and the epigenome

Abstract: The epigenetic phenomena refer to heritable changes in gene expression other than those in the DNA sequence, such as DNA methylation and histone modifications. Major research progress in the last few years has provided further proof that environmental factors, including diet and nutrition, can influence physiologic and pathologic processes through epigenetic alterations, which in turn influence gene expression. This influence is termed nutritional epigenetics, and one prominent example is the regulation of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 69 publications
0
43
0
1
Order By: Relevance
“…Vitamin A is an essential fat-soluble vitamin and adequate daily intake (~700–900 μg for humans) and hepatic storage (~80% in a healthy individual) are required to maintain plasma retinol levels around 2 μmol/L in humans (1–2 μmol/L in rodents) [ 2 , 3 ]. Vitamin A plays important physiological roles in vision, reproduction, growth, development, immunity, and metabolic programs [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Most functions of vitamin A are mediated through the activation of ligand-activated transcription factors.…”
Section: Vitamin a Its Active Metabolites And Dietary Causes Of mentioning
confidence: 99%
“…Vitamin A is an essential fat-soluble vitamin and adequate daily intake (~700–900 μg for humans) and hepatic storage (~80% in a healthy individual) are required to maintain plasma retinol levels around 2 μmol/L in humans (1–2 μmol/L in rodents) [ 2 , 3 ]. Vitamin A plays important physiological roles in vision, reproduction, growth, development, immunity, and metabolic programs [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Most functions of vitamin A are mediated through the activation of ligand-activated transcription factors.…”
Section: Vitamin a Its Active Metabolites And Dietary Causes Of mentioning
confidence: 99%
“…Nutritional factors which influence mineral homeostasis, differentiation of the osteoblasts and the immune system, such as vitamin D and vitamin A, have not previously been included in long-term studies of radiographic outcome in JIA [15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that ATRA and its agonists have preventive and therapeutic effects in various experimental kidney diseases by interfering with factors that contribute to renal damage (6,25,40,54). The physiological effects of ATRA and its receptors are mediated by modulating gene expression, which is a dynamic and orchestrated process involving association of receptors with a multitude of coregulators and epigenetic modulators (3,9,61).…”
mentioning
confidence: 99%